2022
DOI: 10.3389/fmolb.2022.1001212
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in the development of knee osteoarthritis: A comprehensive research review

Abstract: Knee osteoarthritis (KOA) is one of the most common degenerative diseases, and its core feature is the degeneration and damage of articular cartilage. The cartilage degeneration of KOA is due to the destruction of dynamic balance caused by the activation of chondrocytes by various factors, with oxidative stress playing an important role in the pathogenesis of KOA. The overproduction of reactive oxygen species (ROS) is a result of oxidative stress, which is caused by a redox process that goes awry in the inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 129 publications
1
38
0
Order By: Relevance
“…Our findings showed a significant increase of ROS in OA sf-MSCs compared with H sf-MSCs, confirming a senescent phenotype in OA cells which could amplify the progression of OA. Although not demonstrated in sf-MSCs, our data agree with the finding of elevated levels of ROS in aged and OA cartilage, both in human and animal models [ 49 ]. Furthermore, cells from human cartilage exposed to hydrogen peroxide showed hallmarks of chondrocyte senescence, such as reduced cell proliferation and lower synthesis of GAG [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings showed a significant increase of ROS in OA sf-MSCs compared with H sf-MSCs, confirming a senescent phenotype in OA cells which could amplify the progression of OA. Although not demonstrated in sf-MSCs, our data agree with the finding of elevated levels of ROS in aged and OA cartilage, both in human and animal models [ 49 ]. Furthermore, cells from human cartilage exposed to hydrogen peroxide showed hallmarks of chondrocyte senescence, such as reduced cell proliferation and lower synthesis of GAG [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among them, synovial inflammation, as an initiating factor, is tied to the pathological aggravation of OA ( Arra et al, 2020 ). Various evidences have indicated that the accumulation of ROS interacts with synovitis and worsens, which may show an important influence in the development of OA ( Liu et al, 2022 ; Sunk et al, 2022 ). Inflammatory reaction exists in synovial tissues, that is, the severity of synovitis is associated with the symptoms of OA and the progress of disease to a large extent.…”
Section: Resultsmentioning
confidence: 99%
“… 11 Synovial inflammation and increased angiogenesis are associated with oxidative stress. 11 , 46 ROS and oxidative stress are elevated in patients with OA. Systemic oxidative stress induces synoviocytes and chondrocytes to produce IL-6, IL-8 and prostaglandins.…”
Section: Discussionmentioning
confidence: 98%
“…The production of cytokines and growth factors by the inflamed synovium may affect the production of degrading enzymes and cartilage loss. 46 , 47 Studies have shown that the viscosity of synovial fluid is reduced and lipid peroxidation is increased in OA patients, suggesting a greater oxidative modification of synovial fluid components by ROS associated with OA. 48 Therefore, we speculate that there is a tendency to change the antioxidant status of synovial fluid in OA patients with increased GPXs activity.…”
Section: Discussionmentioning
confidence: 99%